Business Environmental Analysis with Competitive Profile Matrix Method on Market Optimization in Real Estate Company (A Case Study at Tangerang Selatan Area) - Widiatama, Yulizar; Hamid, Aceng Abdul; Martono, Martono (International Journal of Economics and Financial Issues, 2018)
This study aims to determine the competitiveness of real estate company as well as strategies that can be done company based on the level of importance and performance. The problem that often faced is about the competitiveness of business with other real estate companies that continue to grow. Otherwise, reduced sales turnover among the real estate companies become a serious problem for their financial status. Whereas, the company must make efforts to obtain the market share, change the sales strategy, and improve the concept of the human resource environment to achieve the target set by the company. By analyzing the real estate company’s sales turnover and competitiveness with Competitive Profile Matrix and BCG Matrix method to visualize the existing condition occurred. The results of data processing of sales transactions in August 2015-July 2016 amounted to 569 units, in average, sales made by the company approximately 2 units / day. By observation from 3 Real Estate Companies in Tangerang Selatan showed that August 2015 has the lowest unit sold within the area by only 24 units sold, even though the sales were increasing by September 2015 but the trend are still degrading until July 2016. The study need the correct tools to visualize the problem and turn the result as opportunities for Real Estate Companies in Tangerang Selatan. Meanwhile the EFE Matrix value shows 2.91, IFE Matrix value shows 2.48, the value of IE Matrix shows 2.69. As for the value of Competitive Profile Matrix obtained for 2.56, from GE McKinsey matrix showed the position of real estate at high industry attractiveness quadrant with a score of 3.88 and high business strength position with a score of 3.93. There was a growth rate of 52% and a relative market share of 1.31 using the BCG Matrix. An appropriate strategy for real estate companies in Tangerang Selatan is a market penetration strategy to expanding their business directly to the consumer, product development to enhance the innovative housing product, horizontal integration (integrated horizontal) with the supplier to have economies of scale and joint venue with other business to enhance the markets of their products. Keywords: IE Matrix, Competitive Profile Matrix, BCG Matrix JEL Classifications: M21, R30, R38